2002
DOI: 10.1073/pnas.102173299
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger endothelial cells of vertebrates: A nonperipheral leukocyte system for high-capacity elimination of waste macromolecules

Abstract: I n his pioneering work on the ultrastructure of the hepatic sinusoid 30 years ago, Wisse (1) observed numerous ''smoothwalled macropinocytic vesicles'' in the sinusoidal liver endothelial cells (LEC), suggestive of active pinocytic scavenging of blood plasma proteins. The subsequent finding that the specific activities of lysosomal enzymes in LEC were as high as in the Kupffer cells (2), and for some enzymes even higher, substantiated Wisse's notion. In a series of papers over the next 20 years, it was shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
134
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 28 publications
1
134
0
Order By: Relevance
“…LSECs play a critical role in the endocytotic removal of blood borne soluble macromolecular waste products (Seternes et al, 2002), like AGEs and other modified proteins and lipoproteins and different products from extracellular matrix turnover. Indeed, the present study showed suppressed endocytotic capacity in the old mice, especially in the centrilobular region, suggesting compromised scavenger function in aging SEC and an agerelated reduction in this important clearance function.…”
Section: Effect Of Aging On the Scavenger Function Of Sinusoidal Endomentioning
confidence: 99%
“…LSECs play a critical role in the endocytotic removal of blood borne soluble macromolecular waste products (Seternes et al, 2002), like AGEs and other modified proteins and lipoproteins and different products from extracellular matrix turnover. Indeed, the present study showed suppressed endocytotic capacity in the old mice, especially in the centrilobular region, suggesting compromised scavenger function in aging SEC and an agerelated reduction in this important clearance function.…”
Section: Effect Of Aging On the Scavenger Function Of Sinusoidal Endomentioning
confidence: 99%
“…dead cells, bacteria, large molecular complexes), and they are found in many parts of an animal. In particular, those macrophages residing in close connection to the bloodstream, are highly phagocytic thus functioning as an important element in the reticuloendothelial systemtogether with scavenger endothelial cells in liver of mammals and in the kidney or heart of pisciformes (fish) (Seternes et al, 2002). The endocytic pathway normally confers total degradation of DNA -especially if the DNA is transported to the end-point terminal (lysosomes).…”
Section: Introductionmentioning
confidence: 99%
“…The endocardial endothelial cells (EEC) lining the muscular trabecula of the Atlantic cod (Gadus morhua L.) heart represent a general vertebrate non-phagocytic scavenger endothelial cell (SEC) system with an extensive capacity to endocytose and degrade soluble physiological and foreign macromolecular waste substances/molecules from the circulation by receptormediated endocytosis (Seternes et al, 2002). Functional studies indicate that the cod aEECs express a set of at least four types of functional endocytic receptors for this purpose: (i) the collagen ␣ chain receptor (Koren et al, 1997;Smedsrød et al, 1995), (ii) the hyaluronan receptor (Seternes et al, 2001b;Sørensen et al, 1997a), (iii) the mannose receptor (Sørensen et al, 2001) and (iv) the scavenger receptor (Seternes et al, 2001a;Sørensen et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver sinusoidal endothelial cells (LSECs) are a specialized type of endothelium, lining the liver sinusoids, that use receptor-mediated endocytosis to take up and degrade numerous physiological and non-physiological soluble macromolecules and colloids from the blood [35]. In addition, through their fenestrations, LSECs act as a dynamic filter facilitating the exchange of substrates between blood and hepatocytes [47].…”
Section: Introductionmentioning
confidence: 99%